Peti Gantung Sebagai Media Pembuktian Kebenaran pada Kasus Kematian Tidak Wajar: Studi Kasus - Rechijnce Abigail Bofra; Septian Aji Permana (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to explore the meaning, function, and implementation process of the hanging coffin tradition practiced by the indigenous community of Kampung Ibe, Tambrauw Regency, Southwest Papua, particularly in cases of deaths considered unusual or suspicious. The hanging coffin ritual serves not only as a traditional burial practice but also as a spiritual medium through which the cause of death is interpreted based on signs believed to be conveyed by the deceased’s spirit. This research employs a naturalistic qualitative approach, utilizing observation, in-depth interviews, and documentation involving customary leaders, tribal chiefs, community elders, and families who have performed the ritual. The findings reveal that the community places greater trust in the spiritual signs manifested through the ritual than in medical results or formal legal explanations. The stages of the ritual provide progressively clearer interpretations for the community, ultimately leading to a culturally accepted conclusion regarding the cause of death. The hanging coffin tradition also strengthens social solidarity, maintains the balance between the living and ancestral spirits, and functions as a mechanism for resolving conflicts within the community. Thus, this tradition is not merely a burial practice but also a deeply rooted cultural and spiritual system for uncovering truth within the indigenous socio-cultural framework.